Study of Pedicles in Dried Human Lumbar Vertebra : A Morphometric Analysis - Khair, Rummana; Rahman, Zohora Farhana; Jahan, Ishrat; Alam, Sultana Ruma (IAHS Medical Journal, 2022)
Background: In the dynamic part of the spinal column the lumbar vertebra are the largest vertebra that support the maximum body weight and exhibit the greatest degree of degenerative changes. Pedicles of the vertebra act as a port to perform procedures inside the bodies of the vertebra such as biopsies, vertebroplasties or kyphoplasties. Pedicle screw fixation is a technically demanding procedure. Accurate anatomical knowledge of the morphometry of vertebral pedicle are also important for preoperative procedure, planning and in the design and manufacture of pedicle screws. The objective of this study to observe the morphometry of lumbar pedicles to determine the size of the screw in transpedicular screw fixation on the perspective of Bangladesh. Materials and methods: A descriptive observational study was conducted at Southern Medical College and Hospital in the Department of Anatomy on 65 dry adult human lumbar vertebra from December 2020 to May 2021. Width height of pedicle along with antero-posterior diameter of lateral recess (Depth) were observed by using digital Vernier Calipers and after recording data were analysed. Results: The study shows that there is gradual increase in the mean width of the pedicles on both right and left side from L1 to L5. Mean height of the pedicle and antero-posterior diameter of lateral recess both showed decrease at the level of L3 both on the right and left side. Conclusions: The measured data will give a gross measurement of pedicle of lumbar vertebra on Bangladeshi people, hope to provide the clinicians a better support during working with pedicles. IAHS Medical Journal Vol 4(2), December 2021; 51-54